Regioselective one-pot bromination of aromatic amines - Smith, M.B.; Guo, L.; Okeyo, S.; Stenzel, J.; Yanella, J.; LaChapelle, E. (Organic Letters, 2002)
(Matrix Presented) Treatment of aniline with n-butyllithium and then trimethyltin chloride gave the tin amide (PhNH-SnMe3) in situ. Without isolation of the tin amide reaction with bromine and workup with aqueous fluoride ion gave p-bromoaniline in 76% yield, with no dibromoaniline or o-bromoaniline. Application of this sequence to 11 different aromatic amines gave selective bromination in 36-91% yields, without formation of dibromides. This constitutes a good general method for the regioselective bromination of aromatic amines.
37 citations (Crossref) [2023-10-31]
Keywords: article; dept.che

Generation, isolation, and characterization of a stable enol from grignard addition to a bis-ester - Nicaise, O.J.-C.; Ostrom, K.F.; Dalke, B.J. (Journal of Chemical Education, 2005)
1 citations (Crossref) [2023-10-31]
Keywords: Addition reactions; Bis-ester; Characterization; Chemistry; Esters; Experiments; Grignard addition; Infrared spectroscopy; Ketones; Molecular structure; Nuclear magnetic resonance; Organic chemistry; Organometallics; Reaction kinetics; Stable enol; Synthesis (chemical); Temperature dependent formation; Thermodynamic stability; dept.che; peer-reviewed

Bis(benzylsulfanyl)maleonitrile - Backiel, Stanley; Bajrami, Besnik; Hunter, Allen D.; Zeller, Matthias; Lesley, M. J. Gerald (Acta Crystallographica Section E: Crystallographic Communications, 2005)
The title compound, C18H14N2S2, crystallizes as a pseudomerohedral twin, with four independent molecules in the asymmetric unit. The compound shows a combination of π-interactions and close-packing, with the planar maleonitrile and phenyl groups extending into pockets of neighbouring molecules. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00342 tex.type: [object Object]
Keywords: dept.che

1,1′-Dibromoferrocene - Hnetinka, Chrissy A.; Hunter, Allen D.; Zeller, Matthias; Lesley, M. J. Gerald (Acta Crystallographica Section E-structure Reports Online, 2004)
The structural properties of 1,1′-dibromoferrocene, [Fe(C 5H4Br)2, were investigated using single-crystal x-ray diffraction. It was found to crystallize in the non-centrosymmetric space group P21. Despite of the steric demand of the two bromine substituents, the two cyclopentaldienyl (Cp) rings were found to exhibit an eclipsed conformation in the solid state. The conformational arrangement found in compound seems not to be the result of general electronic preference within this class of compounds, but has to be attributed to crystal packing effects in the solid state.
11 citations (Crossref) [2023-10-31] Citation Key Alias: pop00202 tex.type: [object Object]
Keywords: Bromine compounds; Conformations; Crystal packing; Crystal structure; Crystallization; Derivatives; Ligands; Molecular structure; Organometallics; Pseudo-torsion angle; Single crystals; Solid state structures; Synthesis (chemical); X ray diffraction; dept.che

p‐Anisolecarbonitrile - Lesley, M. J. Gerald; Pineau, Mark R.; Hunter, Allen D.; Zeller, Matthias (Acta Crystallographica Section E: Crystallographic Communications, 2004)
The structure of p-anisolecarbonitrile, C8H7NO, was determined by single-crystal X-ray diffraction at 100 K. It crystallizes in the monoclinic space group P21/c with two crystallographically independent molecules in the asymmetric © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00236 tex.type: [object Object]
Keywords: Aromatic rings; Asymmetric units; Bond length; Chemical bonds; Complexation; Crystal atomic structure; Crystal symmetry; Crystallography; Derivatives; Nitrogen compounds; Parallel stacks; Synthesis (chemical); X ray diffraction; dept.che

A gene coding for a novel protein specific to the olfactory rosettes of atlantic salmon - Pang, J.; Lloyd, J.M.; Rhoads, D.E.; Hartman, K.A. (Journal of Biomolecular Structure and Dynamics, 2002)
We have isolated a 1.6 kb clone from a cDNA library made from the olfactory rosettes of th Atlantic salmon (Salmo salar). The clone contains a 1200 bp, open reading frame (name OSC) which codes for a protein with 400 amino-acid residues (Oscp). The mRNA corresponding to OSC is strongly expressed in the olfactory rosettes and weakly expressed in gills but is expressed in only these two tissues. This suggests that Oscp may have a specific and important role in olfaction. The sequence of Oscp suggests that it is not globular. Predictions show only a small fraction of alpha-helix. Oscp is hydrophilic but with the number of positively charged residues equal to the number of negatively charged residues. No closely similar protein can be found on the basis of homology searches or hydrophobicity comparisons. However, a 44 residue segment (G300 through K343) is significantly homologous to a segment of alpha-lactalbumin (G51 through K94). The similarities include the 19 residues of the "alpha-lactalbumin-lysozyme C signature," the ten residues of the Ca2+ binding elbow and the four cysteine residues which provide two key disulfide links in alphalactalbumin and lysozyme C. Two more Cys residues are also very similarly placed. We conclude that the gene OSC codes for a unique protein which most likely contains a specific site for binding Ca2+ and plays a unique role in the signal pathway of olfaction in salmon.
0 citations (Crossref) [2023-10-31]
Keywords: *Calcium-Binding Proteins/ge [Genetics]; *Genes; *Olfactory Pathways/ph [Physiology]; Amino Acid Sequence; Animalia; Animals; Base Sequence; Binding Sites; Calcium; Calcium-Binding Proteins; Calcium-Binding Proteins/ch [Chemistry]; Calcium-Binding Proteins/me [Metabolism]; Calcium/me [Metabolism]; Cloning; Molecular; Genes; Liver; Liver/me [Metabolism]; Molecular Sequence Data; Myocardium; Myocardium/me [Metabolism]; Northern blotting; Olfactory Pathways; Open Reading Frames; Organ Specificity; RNA; Messenger; RNA; Messenger/ge [Genetics]; Salmo; Salmo salar; Transcription; Genetic; animal tissue; article; dept.che; gene expression; gene isolation; nonhuman; olfactory system; open reading frame; priority journal; protein expression; salmon; smelling

syn-2,4-Bis(4-methoxybenzylidene)-trans-1,3-dithexyl-2,4-diaza-1,3-diboracyclobutane - Lesley, M. J. G.; Pineau, M. R.; Nelson, D. M.; Crundwell, Guy (Acta Crystallographica Section E-structure Reports Online, 2007)
In the crystal structure of the title compound, C28H44B2N2O2, the square-planar B2N2 ring is slightly puckered. One of the thexyl groups exhibits disorder over two positions. The site occupancies for the disordered thexyl groups refined to 0.611 (4) and 0.389 (4). © 2007 International Union of Crystallography.
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00366 tex.type: [object Object]
Keywords: dept.che